Unlocking the potential of BIM for transformation in the Kenyan construction industry - Alakhali, Ahmed K.; Baarimah, Abdullah O.; Alkhadri, Aiman H.; Gabir, Adham A.; Hasan, Kamrul; Alawag, Aawag Mohsen (IEEE, 2024)
The adoption of Building Information Modeling (BIM) has emerged as a transformative approach in the global construction industry, enhancing project management, collaboration, and overall efficiency. This review focuses on investigating the potential impact of adopting BIM on the Kenyan construction industry. The Kenyan construction sector faces challenges such as project delays, cost overruns, inadequate communication, and limited collaboration among stakeholders. The review examines how BIM can address these issues by facilitating enhanced visualization, data sharing, and coordination throughout the project life cycle. Through an analysis of existing literature and case studies, this review evaluates the key benefits of BIM adoption, including improved design accuracy, clash detection, and reduced rework. Additionally, it explores the potential hurdles in integrating BIM into the Kenyan context, such as technological barriers, skill gaps, and resistance to change. The review also highlights the role of government policies, industry regulations, and educational initiatives in promoting BIM adoption. Lessons learned from BIM implementation in other countries provide valuable insights into the strategies that can be tailored to the Kenyan construction landscape. In conclusion, this review underscores the potential of BIM to revolutionize the Kenyan construction industry by fostering collaboration, streamlining processes, and ultimately delivering projects more efficiently. By addressing the specific challenges faced by the Kenyan context and leveraging the advantages of BIM, the industry can overcome obstacles and work towards sustainable growth and development.